2021
DOI: 10.1002/adfm.202103171
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Impacts of Engineering Defects and Band Gap Alignment Mechanism on the Catalytic Performance of Holey 2D CeO2−x‐Based Heterojunctions

Abstract: Critical catalysis studies often lack elucidation of the mechanistic role of defect equilibria in solid solubility and charge compensation. This approach is applied to interpret the physicochemical properties and catalytic performance of a free-standing 2D-3D CeO 2−x scaffold, which is comprised of holey 2D nanosheets, and its heterojunctions with MoO 3−x and RuO 2 . The band gap alignment and structural defects are engineered using density functional theory (DFT) simulations and atomic characterization. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…The energy band diagram, discussed subsequently, shows the probable critical importance of the F + (V O • ) and the F ++ (V O x ) color centers, which derive from the intrinsic F 0 color centers (V O •• ), as these facilitate n-type semiconductivity. The presence of these redox reactions and color centers is indicated in the PL data of Figure l, the peaks of which have previously been attributed to these features and the effects of which have been shown to be enhanced by Mo doping. , The same effect, albeit less intense, would occur with substitutional Mo solid solubility. To maintain charge balance, in the absence of O 2 (g), the oxygen vacancies must become neutrally charged and hence F ++ color centers .…”
Section: Results and Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The energy band diagram, discussed subsequently, shows the probable critical importance of the F + (V O • ) and the F ++ (V O x ) color centers, which derive from the intrinsic F 0 color centers (V O •• ), as these facilitate n-type semiconductivity. The presence of these redox reactions and color centers is indicated in the PL data of Figure l, the peaks of which have previously been attributed to these features and the effects of which have been shown to be enhanced by Mo doping. , The same effect, albeit less intense, would occur with substitutional Mo solid solubility. To maintain charge balance, in the absence of O 2 (g), the oxygen vacancies must become neutrally charged and hence F ++ color centers .…”
Section: Results and Discussionmentioning
confidence: 69%
“…The surface XPS data in the Ce 3d orbital are used for distinguishing Ce 3+ (at the binding energy of ∼881 and ∼885 eV) and Ce 4+ (at the binding energy of ∼883, ∼889, and ∼898 eV). The relatively subsurface defect is analyzed by O 1s XPS measurements of O–Ce 3+ (at a binding energy of ∼531 eV) and O–Ce 4+ (at a binding energy of ∼529 eV) because of the higher penetration depth in O compared to that in Ce. , For CeO 2– x , Figure d–i shows that the Ce 3+ concentrations ([Ce 3+ ]) were relatively high for CeO 2– x and that sample N 2 exhibited the highest value, again consistent with V O •• formation from atmospheric reduction under N 2 . The partially reversing effect of Mo also is confirmed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar energy position of the absorption edge of the Mo‐doped sample with MoO 2 reference confirmed the dominant Mo 4+ valence state in Fe 2.93 ▫ 0.017 Mo 0.053 O 4 . [ 37,49 ] Thus, the lattice enlargement in the Rietveld refinement was undoubtedly explained by the larger Mo 4+ ions (rMo4+=0.79${r_{M{o^{4 + }}}} = 0.79$Å [ 50 ] versus rFe3+=0.65${r_{F{e^{3 + }}}} = 0.65$Å [ 39 ] ). [ 51 ] Moreover, the absence of the pre‐peak indicated that Mo preferred to occupy at the 16 d sites with higher O h symmetries than 8 a sites with T d symmetries, [ 52 ] which was consistent with DFT results.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 Point defects forming at the surface of the anode materials are the most critical one. 51–53 Point defects such as vacancy will disturb the surrounding atoms to some extent and cause lattice distortion of crystal materials, which can improve their conductivity and the diffusion coefficient by effectively regulating the electronic structure. 53–56 Wang et al 57 synthesized hierarchical SnS 2 microspheres with S vacancy through a one-step solvothermal process.…”
Section: Energy Storage Mechanisms and Challengesmentioning
confidence: 99%